Non-vitamin K antagonist oral anticoagulants in adults with a Fontan circulation: are they safe. Issue 1 (3rd June 2019) - Yang, Hayang; Veldtman, Gruschen R; Bouma, Berto J; Budts, Werner; Niwa, Koichiro; Meijboom, Folkert; Scognamiglio, Giancarlo; Egbe, Alexander Chima; Schwerzmann, Markus; Broberg, Craig; Morissens, Marielle; Buber, Jonathan; et al.
Abstract : Background: In Fontan patients with atrial arrhythmias (AA), non-vitamin K antagonist oral anticoagulants(NOACs) have a class III recommendation according to the Pediatric & Congenital Electrophysiology Society (PACES)/Heart Rhythm Society (HRS) guideline in 2014, due to lack of data on outcomes as opposed to evidence of harm. To address this gap in data, we investigated the safety and efficacy of NOACs in adults with a Fontan circulation in a worldwide study. Methods: This is an international multicentre prospective cohort study, using data from the NOTE (n on-vitamin K antagonist o ral anticoagulants for t hromboe mbolic prevention in patients with congenital heart disease) registry. The study population comprised consecutive adults with a Fontan circulation using NOACs. Follow-up took place at 6 months and yearly thereafter. The primary endpoints were thromboembolism and major bleeding. Secondary endpoint was minor bleeding. Results: From April 2014 onward, 74 patients (mean age 32±10 years (range 18–68), 54% male) with a Fontan circulation using NOACs were included. During a median follow-up of 1.2 (IQR 0.8–2.0) years, three thromboembolic events (2.9 per 100 patient-years (95% CI 0.7 to 7.6)) and three major bleedings (2.9 per 100 patient-years (95% CI 0.7 to 7.6)) occurred in five atriopulmonary Fontan and one total cavopulmonary connection Fontan patients with AA. Fifteen patients experienced minor bleeding episodes (15.8 per 100 patient-years (95% CI 9.1 to 25.2)). In patients (n=37) using vitamin K antagonists (VKAs) prior to the initiation of NOAC, annual incidence of historical thromboembolic events and major bleeding were 2.4% (95% CI 0.4% to 7.4%) (n = 2) and 1.2% (95% CI 0.7% to 5.1%) (n = 1), respectively. Conclusions: In this review of the largest Fontan cohort using NOACs with prospective follow-up, NOACs appear to be well tolerated and their efficacy and safety during short-term follow-up seem comparable to VKAs. Longer term data are required to confirm these promising short-term results.